Climate resilient development participatory solutions from developing countries (London Routledge, 2014)
The concept of resilience currently infuses policy debates and public discourse, and is promoted as a normative concept in climate policy making by governments, non-governmental organizations, and think-tanks.
"Earthscan from Routledge."
Keywords: Environmental policy -Economic aspects -Developing countries